Influence of paratypical factors on milk quality indicators with different keeping methods - Admin, O.; Admina, N. (Scientific Progress & Innovations, 2022)
The aim of this study was to determine the effect of paratypic factors on cow productivity, somatic cell content in milk and the incidence of mastitis in cows. A total of over 15,000 milk samples were analysed from tethered keeping cows and over 16,000 samples from untethered keeping cows. The average somatic cell content in milk in untethered keeping was 700±11,000/cm3 with a variability of 141 %, and in the case of tethered keeping, it was 411±7,000/cm3 with a very high variability of 209 %. The high values of variability are due to a binomial distribution of somatic cell content. The study determined the strength of the effect of cow age, lactation stage and season of the year on daily milk yield and milk quality of cows. The cows of the first lactation in untethered keeping had the lowest number of somatic cells (545±19.3 thousand/cm3). As the age of animals increased, the value of this indicator first increased until the third lactation (805±28.4 thousand/cm3), and then the average number of somatic cells in milk remained almost at the same level. In tethered keeping conditions content of somatic cells in cows of sixth lactation and older (634±53.1 thousand/cm3) were almost twice as high as in first-born cows (331±9.2 thousand/cm3). The incidence of mastitis in tethered keeping was 17.3±2.33 % in the first month of lactation and decreased to 15.1±2.39 % in the second. Then, during lactation, the number of cows affected by mastitis increased to 21.5±2.24% in the 11th month of lactation (P<0.05). In the untethered keeping, the lowest percentage of mastitis cases was in the second month of lactation (26.9±1.71 %). Later in lactation, the number of cows with mastitis increased to 31.2±1.74 % (P<0.05). As for seasonal changes of milk parameters in untethered keeping, the average daily yield varied from 15,8±0,14 kg in January to 17,8±0,16 kg in June, fat content varied from 3,39±0,011 % in June to 3,71±0,010 % in December, protein content – from 3,00±0,009 % in September to 3,23±0,010 % in March. The lowest somatic cell content was observed in milk samples obtained in January (380±14.2 thousand/cm3), and the highest - 703±17.1 thousand/cm3 in July. In untethered keeping conditions the highest frequency of mastitis detection was observed in summer months (43,0±2,12 %, 48,6±2,14 % and 41,8±2,11 %), and also in March (36,8±2,08 %) and November (33,0±1,19 %). The obtained results can be used for the prevention of mastitis in cows, which can be a cost effective method for the control of milk quality and safety in modern conditions.